2014
DOI: 10.1016/j.drugalcdep.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain differences in alcohol-dependent individuals with and without comorbid substance dependence

Abstract: Background Over 50% of individuals with alcohol use disorders (AUD) also use other substances. Therefore, brain structural abnormalities observed in alcohol dependent individuals may not be entirely related to alcohol consumption. This MRI study assessed differences in brain regional tissue volumes between short-term abstinent alcohol dependent individuals without (ALC) and with current substance use dependence (polysubstance users, PSU). Methods Nineteen, one-month-abstinent PSU and 40 ALC as well as 27 lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 60 publications
(86 reference statements)
2
30
0
2
Order By: Relevance
“…Both alcohol dependent groups had smaller GM compared to HC, but only ADO had larger CSF. GM volume reductions have been reported in both alcohol dependent individuals (Mon et al, 2014) and polysubstance users (Liu et al, 1998). Despite both ADO and PS having decreased GM, only the ADO individuals had increased CSF compared to HC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both alcohol dependent groups had smaller GM compared to HC, but only ADO had larger CSF. GM volume reductions have been reported in both alcohol dependent individuals (Mon et al, 2014) and polysubstance users (Liu et al, 1998). Despite both ADO and PS having decreased GM, only the ADO individuals had increased CSF compared to HC.…”
Section: Discussionmentioning
confidence: 99%
“…There was also decreased volume in the right thalamus in both ADO and PS individuals, and decreased left thalamic volume in PS individuals. Several studies have reported reductions in thalamic volume in AD individuals (Fein and Fein, 2013; Kril et al, 1997; Mon et al, 2014), and thalamic volume has been shown to negatively correlate with alcohol consumption (Kril et al, 1997). Thalamic volume reductions have been reported in individuals with alcohol dependence and comorbid psychostimulant dependence (Mon et al, 2014), however another study investigating a similar population did not find a decrease in thalamus volume (Fein and Fein, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This distinction was made due to evidence showing that individuals dependent on alcohol and drugs have more severe psychopathology, 34 and differences in brain function 44 and structure 45 compared with individuals dependent on alcohol alone. Control participants with a history of heavy alcohol or drug use were also excluded due to known associated functional and structural abnormalities.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%